PENGARUH KARAKTERISTIK KOMITE AUDIT DAN KUALITAS AUDITOR EKSTERNAL TERHADAP MANAJEMEN LABA - Margareth A. R. Sihombing; Herry Laksito (Diponegoro Journal of Accounting, 2017)
This research aims to analyze the effect of audit committee characteristics and external auditor quality on earnings management. The audit committee characteristics analyzed in this research are audit committee size, audit committee expertise, the number of meetings of the audit committee, and the tenure of audit committee chairman. The audit committee characteristics and external auditor quality are the independent variables in this research and earnings managements as the dependent variable. The data in this research were obtained from secondary data from annual report and financial report published by public companies. The companies used as the sample in this research are non-financial companies listed in Indonesia Stock Exchange (IDX) on 2013-2015. This research uses a sample of 147 public companies with the total observation is 441 observations. This research uses the OLS statistic regression to analyze the effect of independent variables on the dependent variable. These research findings show that audit committee size, the number of meetings of the audit committee, and the tenure of audit committee chairman have a negative significant effect on earnings management. Meanwhile, external auditor quality has a negative insignificant effect on earnings management and audit committee expertise has a positive insignificant effect on earnings management.